A Sandwich‐type Electrochemiluminescence Aptasensor for Thrombin Based on Functional Co‐polymer Electrode Using Ru(bpy)32+ Doped Nanocomposites as Signal‐amplifying Tags. Issue 8 (22nd May 2019) - Shan, Yanqun; Jin, Xin; Gong, Miao; Lv, Liangrui; Li, Linyu; Jiang, Meng; Wang, Xiaoying; Xu, Jun
Abstract: Herein, a signal‐on sandwich‐type electrochemiluminescence (ECL) aptasensor for the detection of thrombin (TB) was proposed. The graphene (GR) doped thionine (TH) was electropolymerized synchronously on the bare glassy carbon electrode (GCE) to form co‐polymer (PTG) electrode. The gold nanoparticles (AuNPs) were decorated on the surface of the PTG by in‐situ electrodeposition, and the functional co‐polymer (PTG‐AuNPs) electrode was utilized as sensing interface. Then, TB binding aptamer I (TBA I) as capture probes were modified on the PTG‐AuNPs electrode to capture TB, and Ru(bpy)3 2+ /silver nanoparticles doped silica core‐shell nanocomposites‐labeled TB binding aptamer II (RuAg/SiO2 NPs@TBA II) were used as signal probes to further bind TB, resulting in a sandwich structure. With the assistant of silica shell and AgNPs, the enrichment and luminous efficiency of Ru(bpy)3 2+ were significantly improved. Under the synergy of PTG‐AuNPs and RuAg/SiO2 NPs, the ECL signal was dramatically increased. The proposed ECL aptasensor displayed a wide linear range from 2 fM to 2 pM with the detection limit of 1 fM, which is comparable or better than that in reported ECL aptasensors for TB using Ru(bpy)3 2+ and its derivatives as the luminescent substance. The excellent sensitivity makes the proposed aptasensor a promising potential in pharmaceutical and clinical analysis. Abstract :